How Does the Central Nervous System Control Forthcoming Movement with Different Emotional Stimuli?. Issue 2 (April 2022) - Chikh, Soufien; Mguidich, Hajer; Souissi, Hichem; Watelain, Eric
Maintaining postural balance is a key factor in human motor skills, based in part on emotional stimuli. Our objective in this study was to measure the effect of emotion on postural control as influenced by the direction of forthcoming movement. Eighteen right-handed women initiated a step forward or backward or remained in a static position after visualizing an emotional stimulus (positive, negative, or neutral). Center of pressure (COP) parameters (2D velocity, Medio-lateral (ML), and antero-posterior (AP) amplitude) were recorded for 3-second windows for movement direction and emotional stimulus. We observed a motion * direction effect on 2D velocity, characterized by a decrease in the emotional stimulus and static direction windows. The participants' ML amplitude was influenced by direction, and their reduced amplitude was evident in the presence of emotions. AP amplitude was high in the direction versus emotion window. In the static position, the AP amplitude was high in the direction window and low in the emotion window. The participants' movement planning and programming phase (direction window) was characterized by less oscillation for forward or backward movements and more oscillation before movement, suggesting anticipatory postural adjustments in the emotion window. Static direction was characterized by low oscillation, compared to forward and backward movement and in negative versus positive emotional context, proving the interactive impact of direction and emotion on COP amplitudes. Thus, postural control was influenced by both movement (direction) and emotional content (valence). This study provided insight regarding the interactive effect of emotion and direction on planning and programming forthcoming movement.